Public Opinion, The “No Viral, No Justice” Phenomenon, and Its Impact on the Vina Cirebon Case - Mukhammad Sahlan (Indonesian Journal of Advanced Research, 2026)
This paper aims to analyze the influence of public opinion and the phenomenon of no viral ni justice in handling the legal case of the murder of Vina Cirebon, which went viral and attracted public attention since the release of the film Vina: Before Seven Days. After the film, public pressure arose to reveal the Vina case, which was allegedly full of irregularities. The research method used was qualitative research. The results of this study are that public opinion influenced the re-opening of the Vina Cirebon case, which also gave rise to the phenomenon of no viral, no justice, which also initiated a re-investigation of this case until the Community movement to free her and sue Pegi Setyawan as the main perpetrator, which was later successful. Public opinion in monitoring the Vina Cirebon case has become one of the massive and large movements in law enforcement in Indonesia.